Sub-10 nm features obtained from directed self-assembly of semicrystalline polycarbosilane-based block copolymer thin films - Aissou, Karim (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.